Uncovering learning poverty in mathematics classrooms: Linking learning gaps, instructional practices, and teacher professional learning through SUPER-LS program and slow pedagogy - Fitriati, Fitriati; Novita, Rita; Hidayat, Arif; Khairunnisak, Cut (Journal on Mathematics Education, 2026)
Mathematics learning poverty remains a pressing challenge in Indonesia, where a substantial proportion of students fail to attain curriculum-level conceptual understanding. Although national and international large-scale assessments have documented the scope of this problem, comparatively little research has examined how mathematics learning poverty manifests at the classroom level in terms of students’ conceptual thinking, instructional practices, and teachers’ professional learning needs. Addressing this gap, the present study conducts a classroom-based needs analysis to investigate mathematics learning poverty and to explore how a school–university partnership mediated through lesson study (SUPER-LS), informed by principles of slow pedagogy, may offer a context-sensitive response. A convergent mixed-methods design was employed. Quantitative data were collected through diagnostic assessments administered to 336 Grade 8 students, while qualitative data were obtained from structured observations of 12 mathematics lessons and semi-structured interviews with six mathematics teachers. Quantitative results indicate substantial conceptual deficits (M = 32.57 out of 100, SD = 17.45), particularly in fractions and algebraic expressions. Analysis of student responses reveals systematic misconceptions and fragile conceptual understanding rather than random error. Classroom observations further show predominantly teacher-centered and fast-paced instructional practices, with limited opportunities for student questioning, reasoning, and reflective engagement. Teacher interviews highlight a strong commitment to improving student understanding, alongside constraints related to instructional time, workload, and examination pressures. Taken together, these findings demonstrate that mathematics learning poverty emerges from the interaction of student-level misconceptions, instructional practices, and structural conditions. The study provides an empirical foundation for designing diagnostic-informed professional learning. Within this context, SUPER-LS and slow pedagogy function as context-responsive frameworks to support deeper mathematical learning, collaborative teacher inquiry, and more reflective instructional practices aimed at mitigating mathematics learning poverty.